ANALISIS KOMPARATIF KELEBIHAN DAN KELEMAHAN METODE EVALUASI DALAM PEMBELAJARAN SENI TARI - Deskariani, Uci; Astuti, Fuji; Yuliasma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
His paper analyzes several assessment approaches employed in dance education by comparing their educational benefits and inherent limitations. The study aims to provide insight into how specific evaluation techniques influence learners’ achievements in dance learning contexts. Using a qualitative literature review design, this research synthesizes academic sources discussing performance-based assessment, product evaluation, project assessment, and portfolio assessment. The review indicates that each assessment approach contributes differently to students’ artistic growth, technical mastery, creativity, and reflective capacity. However, challenges also arise in terms of objectivity, time efficiency, and standardization. The study concludes that combining multiple assessment strategies is necessary to ensure a comprehensive and fair evaluation of dance learning outcomes